Penerapan Proxy Server Pada Jaringan Internet Di Kantor Camat Selebar - Aptrio, Zendi; Khairil, Khairil; Supardi, Reno (UNIVED Press, 2025)
Internet utilization in the government sector, especially at Selebar Sub-District Office of Bengkulu City, has been implemented to help in managing administrative data, search for information by browsing, and assist with reporting. Internet access at Selebar Sub-District Office of Bengkulu City uses the Indihome provider which can be accessed by every staff employee. The implementation of Proxy Server on internet network at Selebar Sub-District Office was built using the Linux Ubuntu Server operating system. The proxy server is implemented by filtering social media websites such as Facebook, YouTube, Instagram, Twitter, TikTok and others. Besides that, filtering is also carried out based on working hours and rest hours. The implementation of Proxy Server on the internet network at Selebar Sub-District Office can create a conducive process of managing the administrative system and searching for information and can help filter social media websites so that the work of staff employees is not disturbed and administrative management can be carried out without interruption. Based on the tests that have been carried out, it can beconcluded that the implementation of proxy server on the internet network atSelebar Sub-District Office is running well and is able to restrict access to severalwebsites, but for VPN access it can still access social media.